An Evaluation of the Genotoxicity and Subchronic Oral Toxicity of Synthetic Curcumin - Damarla, Sreenivasa Rao (J Toxicol, 2018)
A battery of toxicological studies was conducted in accordance with international guidelines to investigate the genotoxicity and repeated-dose oral toxicity in rats of synthetic curcumin (VEAMIN 99, >99% purity). There was no evidence of mutagenicity in a bacterial reverse mutation test, whereas an in vitro mammalian chromosomal aberration test was positive for induction of chromosomal aberrations which is in line with results reported for natural curcumin. There was no evidence of genotoxicity in an in vivo mammalian micronucleus test. Synthetic curcumin did not cause mortality or toxic effects in a 90-day repeated-dose oral toxicity study at daily doses of 250, 500, or 1000 mg/kg body weight (bw)/day (administered by gavage in a split dose). The no observed adverse effect level (NOAEL) determined from the 90-day study was 1000 mg/kg bw/day for both male and female Wistar rats.